Ecoinnovations and sustainable development - Chrząścik, Ireneusz; Marciniuk-Kluska, Anna; Kluska, Mariusz (Studia Ecologiae et Bioethicae, 2010)
This work presents the issues concerning connections between eco-innovations and sustainable development in Poland and the European Union. Innovations and sustainable development are of fundamental importance for the growth in the economy. Sustainable development has been one of the European priorities for a long time. At present, it has acquired new significance in the light of the crisis connected with climate changes and the extensive financial crisis prevailing mainly in the USA and Europe. Still, it is a great challenge for EU cities and regions. Also examined were little cooperation between entrepreneurs and people of science in the processes introducing modern technologies and expenditure on innovations.